Place attachment mediating perceived destination competitiveness and visitors’ intention in ethnic enclave tourism destination in Brickfields, Malaysia - Raju, Munieleswar; Kunasekaran, Puvaneswaran; Subramaniam, Thanam; Chia, Kei Wei (Universiti Putra Malaysia, 2025)
This study explored the factors influencing local tourists' intention to visit and explore an ethnic enclave. The research focused on Little India in Brickfields, a historic area known for its British colonial architecture with structures that have endured for over a century. The investigation examined the influence of perceived destination competitiveness and place attachment on tourist’ intention to visit ethnic enclave-related tourism destinations. The study employed a positivist research philosophy and quantitative methods to collect data. A sample of 407 domestic tourists who visited Little India Brickfields was targeted for this study. The Cochran formula was applied to calculate the sample size due to the unavailability of information regarding the population. The study’s outcomes indicated that perceived destination competitiveness is insignificant to travel intentions. Similarly, place attachment does not mediate between domestic tourists’ perception of destination competitiveness and their visit intention. Specifically, this study contributes to the perceived destination competitiveness and attachment theory literature with the integration of ethnic enclave tourism nexus.